The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0168815
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Aerosolized Bacterial Viruses to Four Germicidal Products

Abstract: Viral diseases can spread through a variety of routes including aerosols. Yet, limited data are available on the efficacy of aerosolized chemicals to reduce viral loads in the air. Bacteriophages (phages) are often used as surrogates for hazardous viruses in aerosol studies because they are inexpensive, easy to handle, and safe for laboratory workers. Moreover, several of these bacterial viruses display physical characteristics similar to pathogenic human and animal viruses, like morphological size, type of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The results presented in [58], who used the same environmental chamber setup. The only notable difference is with φ6 at low RH, which did not become inactivated even after a 2-hour exposure to the reference conditions [45]. It remained infectious after a 6-hour and a 14-hour exposure, but there was more variability in RIR replicates [58].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The results presented in [58], who used the same environmental chamber setup. The only notable difference is with φ6 at low RH, which did not become inactivated even after a 2-hour exposure to the reference conditions [45]. It remained infectious after a 6-hour and a 14-hour exposure, but there was more variability in RIR replicates [58].…”
Section: Discussionmentioning
confidence: 92%
“…Currently, there are no air treatment strategies available for inactivating airborne viruses during viral hospital outbreaks, which is due to the lack of approved protocols. UV light, ozone and disinfecting agents have been tested for airborne phage and virus inactivation [43][44][45][46], but none of them have led to the establishment of standardized air treatment protocols. In addition, they were used for short periods of time (� 1 minute) and many were at high concentrations that are toxic for humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a primer-probe set, set A, for PCR to robustly quantify phi-X174-specific airborne particles without being adversely affected by UV. Duchaine s research group had used another primer-probe set, set B Turgeon et al, 2014;Verreault et al, 2015;Turgeon et al, 2016. Ho et al 2016 had reported that the log reduction by UV of phi-X174 gene copies increased as the specific amplicon length for PCR increased.…”
Section: Behavior Analysis Of the Phage Aerosol At Different Levels Omentioning
confidence: 99%
“…Additionally, as viruses of bacteria, phages pose little risk to workers or animals when used in aerosolization tests for research purposes. PhiX174 is a single stranded DNA, non-enveloped, 25 nm bacteriophage that infects E. coli and has been previously used in aerosolization and ozonation experiments and has established propagation and quantification protocols (Tseng and Li 2006;Turgeon et al 2016;Turgeon et al 2014).…”
Section: Introductionmentioning
confidence: 99%